Natures Chorus: Determining Avian Richness across Microhabitats using AudioMoths - Bates, Madelyne; Bray, Cassandra; Koblensky, Isabelle; Baran, Mark; Garneau, Danielle (2024)
Bird surveys are commonly actively performed using point count techniques; however, more recently, passive acoustics have become a complementary method to evaluate species richness and trends across microhabitats. Traditional methods like point counts may lead to biases in data records depending on the researcher's experience level. Autonomous recording devices (ARU), such as AudioMoths, are an affordable method for those studying avifauna to add to their toolbox. Confidence in rare species identification may increase by being able to leave AudioMoths out for a longer duration than feasible with traditional point counts and the ease with which artificial intelligence program workflows can attempt species confirmation. In the fall of 2024, we performed both passive (ARU) and active (point count) avifauna surveys across three microhabitats (e.g., wetland, forest, meadow) at Point au Roche State Park. Our active surveying method used binoculars and Merlin Bird ID to help identify species for three-10-minute intervals during each visit. Our passive surveying method used AudioMoths to record vocalizations deployed for seven days, recording during peak hours from 20:00-8:00. BirdNet-Analyzer was used to identify vocalizations from audio files. Species richness was greatest in the meadow (51) and wetland (47) and least in the forest (27). Merlin Bird ID recorded black-capped chickadee (Poecile atricapillus), Canada goose (Branta canadensis), northern cardinal (Cardinalis cardinalis), blue jay (Cyanocitta cristata), and downy woodpeckers (Picoides pubescens) across the sites. The American crow (Corvus brachyrhynchos) and barred owl (Strix varia) called abundantly at the wetland (43%) and the meadow (36%) sites, while the forest site was more limited. Avian community similarity was greatest between the wetland and meadow (64%) microhabitats. Other notable species observed are stripe-faced meadow katydid (Orchelimum concinnum), wood frog (Lithobates sylvaticus), and spring peeper (Pseudacris crucifer). We highlight the ...